O rosto misterioso : memória material num objecto anónimo de uma sacerdotisa de Amon (ataúde A.4 da Sociedade de Geografia de Lisboa) - Sousa, Rogério (2013)
An anonymous object tends to be viewed as an object devoid of memory. In the case of the anthropomorphic coffin belonging to an Egyptian priestess of Amon from the 21st dynasty, the identity of its owner has been lost forever. However, as an object, this coffin reflects a centuries-old funerary tradition and it is an authentic repository of a collective material memory that, at the time it was built, was already thousands of years old. Each of its elements was integrated into the coffin in accordance with a sequence and a coding that we could say «phylogenetic», in the sense that, when it was inscribed on the object, it repeated the material evolution of the coffins themselves. However, given the importance of funerary material culture in ancient Egypt, this process could not be static on the contrary, each new object was always a fresh opportunity to update the design of coffins. Looked at from this perspective, the anonymous coffin A4 of the Sociedade de Geografia de Lisboa is an object of memory that contains within it an ancient material memory that we propose to recover in this paper.